Factors Affecting Stock Returns with Corporate Governance as a Moderation Variable in Manufacturing Companies Listed on The Stock Exchange Indonesia - Vifky Choirun Nissa; Nurshadrina Kartika Sari; Nanda Widaninggar (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
This research aims to analyze the factors that influence returns share. The sample used in this research is manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. The independent variables in this research are PBV, PER, DPR, operating cash flow and accounting profit, where the dependent variable is return shares and adding the corporate governance (CG) moderating variable. By using a purposive sampling method, the author obtained a research sample of 6 manufacturing companies from a research population of 18 manufacturing companies. The data analysis models used in this research are descriptive statistical tests, classical assumption tests, multiple linear regression tests, hypothesis tests and MRA. The results of this research prove that PER, PBV, and operating cash flow have an influence on stock returns However, DPR and accounting profits have no influence on stock returns the audit committee variable moderates the DPR variable on stock returns and the audit committee variable does not moderate PER, PBV, accounting profit and operating cash flow on stock returns